EFFORTS TO IMPROVE THE ABILITY OF WRITING SIMPLE PARAGRAPH IN INDONESIAN SUBJECTS USING STUDENT IMAGE SERIES CLASS III MIS AL QUBA MEDAN - Gemala Widiyarti (SENSEI RESEARCH CENTER, 2022)
In an effort to realize an increase in students' writing, teachers are expected to be able to choose and apply instructional media that can convey learning objectives well to students. The formulation of the problem in this study is whether the application of serial picture media can improve the ability to write simple paragraphs in Indonesian class III students, for example. Al Quba Medan. The purpose of this study was to find out and describe the learning outcomes in the form of the ability to write simple paragraphs using picture series media in Indonesian language learning class III III Mis. Al Quba Medan. This study uses Classroom Action Research (CAR). The data obtained from qualitative data and quantitative data. Data collection techniques through student observation to determine the increase in student learning activities, tests to determine student learning outcomes and documentation. The method of data analysis in this study uses qualitative and quantitative analysis. Based on the results of data analysis it is known that after the picture series media is applied the students' writing ability has increased, this can be seen from the average student learning activity in cycle I of 63.1% and cycle II of 82%. Experiencing an increase from cycle I to cycle II of 18.9%. Students' writing ability has increased after applying serial picture media in the learning process. This can be seen from the increase in student completeness in cycle I of 68.2% and cycle II of 84.21%. Experiencing an increase from cycle I to cycle II by 20%.